Assessing cultural-spatial change in European border areas - Heidi Fichter-Wolf (Belgeo)
This article presents a theoretical approach to the empirical reconstruction of cultural-spatial change, building on knowledge sociology and social constructivism. A model with visualization is presented based on the assumption that cultural-spatial change in European border areas occurs within a process of interaction and communication between different cultures which have their own specific knowledge systems and related social practices. Border regions in this sense are regarded as “spaces with opportunities” that – in the context of neighbourhood cooperation and intercultural communication processes – provide particular opportunity structures for different cultures moving towards each other. Such a view means that border spaces thus have the potential to integrate different social interpretations of reality and within this process cultural-spatial change may take place.